2014
DOI: 10.3109/02699052.2014.947632
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural ratings of self-regulatory mechanisms and driving behaviour after an acquired brain injury

Abstract: It is recommended that self-regulatory measurements should regularly be considered in the driving assessments after ABI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 73 publications
0
18
0
3
Order By: Relevance
“…2,3,11 These findings concur with the relationship between self-reported executive difficulties observed via the BRIEF and its relationship with driving deficits in adult clinical populations. 20,21 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2,3,11 These findings concur with the relationship between self-reported executive difficulties observed via the BRIEF and its relationship with driving deficits in adult clinical populations. 20,21 …”
Section: Discussionmentioning
confidence: 99%
“…Refer to Table 1 for further demographics. Following previous findings from Rike, Ulleberg, Schultheis, Lundqvist, Schanke 20 who found moderate correlations between the BRIEF and self-reported driving outcomes, an a-priori power calculation was conducted to determine minimum sample size to achieve adequate power for point-biserial correlations 24 . To obtain a moderate correlation at 80% power, a minimum of 44 participants was required, making our sample large enough to detect moderate to medium size effects.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…17 Numerous studies have documented decreased community integration among individuals with TBI in key life domains such as employment, 18,19 leisure activities, 7,12,20 ability to live independently, 7,12 and ability to drive. 7, 21 Corrigan and colleagues found that community integration, as assessed by the Community Integration Questionnaire (CIQ), was relatively stable over the first five years after TBI. 22 The CIQ total score was systematically 1.5 standard deviations lower than the normative population, indicating a permanent reduction in community integration after TBI.…”
Section: Introductionmentioning
confidence: 99%